Efektivitas Dan Efisiensi Penggunaan Aplikasi Sobat BPS Dalam Melakukan Rekrutmen Dan Seleksi Calon Mitra BPS Di Badan Pusat Statistik Kota Palu - Agus Sutrisno; Annisah Annisah; Suryadi Hadi (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
The recruitment and selection activities for prospective partners at BPS (Central Statistics Agency) involve a process of seeking and acquiring applicants capable of collaborating with government institutions. Various recruitment and selection methods for BPS partner candidates are commonly employed by government agencies, including job postings, employee recommendations, collaboration with universities, advertisements, and so forth. However, with the current technological advancements, the internet has become a widely used medium for job seekers. One of the methods in use today is through the use of applications. The effectiveness and efficiency of using applications in the recruitment and selection of BPS partner candidates aim to determine how well these applications perform in the process at the BPS Palu Central Statistics Agency. This research is qualitative in nature with a descriptive approach. Data collection techniques involve observation and interviews with prospective BPS partners in Palu. The results of these methods indicate that the effectiveness and efficiency of using applications in the recruitment and selection process for partner candidates are highly effective. This is evident in the significant number of applicants who register and the smooth execution in line with the application's usage. Prospective partners are targeted accurately, understand the program, adhere to timelines, and bring about tangible changes. Any shortcomings, issues, or obstacles in using the application can be resolved effectively, although challenges such as server website downtime need improvement to optimize the application for recruiting BPS partner candidates.